IDE MOBIL NASIONAL SEBAGAI SIMBOL PERLAWANAN TERHADAP NEOKOLONIALISME DI ERA GLOBALISASI - Irhandayaningsih, Ana (Faculty of Humanities, Diponegoro University, 2011)
The immediate popularity of Kiat Esemka is an indication of peopleâ€™s rejection to neocolonialism of the global era. Globalization is identical with capitalism, the root of neo-colonialism. As a not-yet-developed country, Indonesia is often victimized by the free market system, leaving her people disempowered through consumptivism. But eventhough globalization is such a strong trend, due to its lack of values, people are still adhered to nationalism, as a sentiment relevant and useful to protect their identity and sustenance. The idea of creating a national car embodies this spirit of anti-colonialism. Â http://ejournal.undip.ac.id/index.php/humanika/article/view/2909